2019
DOI: 10.1002/hed.26056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patterns and risk factors regarding the onset of nodules in the contralateral thyroid lobe during follow‐up ultrasonography among patients after unilateral lobectomy for the treatment of papillary thyroid carcinoma

Abstract: Background: This study tries to find the patterns of new nodules in contralateral thyroid lobe among papillary thyroid carcinomas (PTCs) after lobectomy using ultrasonography. Methods: Of note, 456 PTCs were enrolled. Clinicopathological features of primary tumors and sonographic patterns of new nodules in contralateral lobe were documented. Logistic regression analysis was performed to identify risk factors for new nodules.Results: The overall incidence of new nodules was 41.9%. 96.3% of new nodules were no g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Consistent with the study from Ritter et al ( 15 ) and Sun et al ( 41 ), we proved that low-risk PTC patients with contralateral benign or nonsuspicious nodules have a low risk of developing clinical contralateral PTC. Our results further suggest that benign or nonsuspicious nodules in the contralateral lobe do not increase the risk of recurrence and disease-specific death.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the study from Ritter et al ( 15 ) and Sun et al ( 41 ), we proved that low-risk PTC patients with contralateral benign or nonsuspicious nodules have a low risk of developing clinical contralateral PTC. Our results further suggest that benign or nonsuspicious nodules in the contralateral lobe do not increase the risk of recurrence and disease-specific death.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a recent study by Sun et al. ( 41 ) showed that patients without nodules in the contralateral thyroid lobe at the time of initial lobectomy had a high probability, up to 41.9%, of developing nodules in the contralateral lobe, but only 6.5% of these nodules were proven to be clinically malignant. The rest of ultrasonically nonsuspicious new nodules achieved favorable clinical outcomes under ultrasound surveillance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%